2022
DOI: 10.2147/prbm.s379000
|View full text |Cite
|
Sign up to set email alerts
|

How Family Supportive Supervisor Behaviors Enhance Employees’ Work-Family Enrichment? Thriving at Work as Mediator and Intrinsic Motivation as Moderator

Abstract: Purpose From the perspective of the work-home resource model, the present research aims to investigate the effect mechanism of family supportive supervisor behaviors (FSSB) on work-family enrichment. Sample and Method Based on 316 Chinese employees’ samples, this study takes the multiple linear regression technique to test our hypothesis model. Results Our study reveals that FSSB is positively related to work-family enrichment. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Based on research that examines the relationship between family-supportive supervisor behavior (FSSB) and individual prosocial and extrinsic motivation at work, covering research areas in four countries, namely Brazil, Kenya, the Netherlands, and the Philippines, the results show that FSSB has a positive relationship with prosocial and extrinsic motivation (Bosch et al, 2018). The positive impact of FSSB on prosocial and extrinsic motivation applies across cultures (Shen et al, 2022). Thus, this study formulates the following hypothesis: H6: Family-supportive supervisor behavior has a positive effect on motivation.…”
Section: Relationship Of Family-supportive Supervisor Behaviour and M...mentioning
confidence: 99%
“…Based on research that examines the relationship between family-supportive supervisor behavior (FSSB) and individual prosocial and extrinsic motivation at work, covering research areas in four countries, namely Brazil, Kenya, the Netherlands, and the Philippines, the results show that FSSB has a positive relationship with prosocial and extrinsic motivation (Bosch et al, 2018). The positive impact of FSSB on prosocial and extrinsic motivation applies across cultures (Shen et al, 2022). Thus, this study formulates the following hypothesis: H6: Family-supportive supervisor behavior has a positive effect on motivation.…”
Section: Relationship Of Family-supportive Supervisor Behaviour and M...mentioning
confidence: 99%
“…A meta-analysis indicated that employee perceptions of general and work-family-specific supervisors and organizational support can have an impact on work-family conflict [ 100 ]. Furthermore, FSSB has been investigated as a mediator of the link between work stress and sensations of exhaustion [ 48 ], and it has been proposed that FSSB may improve workers' work-family enrichment via instrumental and emotional pathways [ 101 ]. In addition, interviews with female e-commerce professionals indicate that FSSB may improve their career sustainability [ 23 ].…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…That is, there is a positive mutual spillover relationship between work and family ( Kopperud et al, 2020 ; Aw et al, 2021 ; Deng et al, 2021 ). Researchers have argued that work-family enrichment, which refers to the beneficial impact of the experiences and resources gained from employees’ involvement in work matters on the quality of family life, can best represent the mechanisms inherent in a positive work-family interface ( Greenhaus and Powell, 2006 ; Gopalan et al, 2021 ; Shen et al, 2022 ). Resources representing one domain help develop personal resources that drive increased outcomes in another domain ( Ten Brummelhuis and Bakker, 2012 ).…”
Section: Introductionmentioning
confidence: 99%